(untitled) (PANGEEA, 2025)
In practice, for small river basins, surface run-off methods are used to simulate extreme hydrological events such as floods. This paper presents the following methods: the unitary hydrograph method and the Mike11-HUM model, which have been calibrated using some computation examples. Once calibrated, they can be used for the analyzed river basins, but also for other river basins with similar physical and geographic conditions.